Applications of Unmanned Aerial Systems in Agricultural Operation Management: Part I: Overview - James Fletcher; Aditya Singh (EDIS)
Unmanned aerial systems (UASs, UAVs, or drones) have emerged as one of the most promising technologies for agricultural operation management in recent decades. This 6-page publication provides an overview of the broad areas where UASs can be utilized for monitoring and managing farm operations. Written by James Fletcher and Aditya Singh, and published by the UF/IFAS Department of Agricultural and Biological Engineering, June 2020.